CASE REPORT OF A PATIENT WITH CYSTINURIA - Matej Kemperle; Robert Kordič; Rina Rus (Slovenska pediatrija, 2020)

(untitled)
Cystinuria is a rare genetic disease characterised by the appearance of kidney stones. Clinically, it is manifested by renal pain, fever or haematuria. In untreated patients, stones may cause urinary tract obstruction and endanger the kidney. The diagnosis is made by a positive family his- tory of cystinuria, if pathognomonic hexagonal crystals of cystine are identified in the urine, or if the analysed stone contains cystine. The initial treatment for cystinuria consists of conservative measures such as increasing fluid intake, limiting sodium and protein intake and urine alkalisation. In addition, medicines containing sulphhydryl groups (e.g. thiopronin, D-penicillamine) are used. Urological surgery is rarely required.